The Suitability of the CdC field Triage for Korean Trauma Care - Kang Kook Choi; Myung Jin Jang; Min A Lee; Gil Jae Lee; Byungchul Yoo; Youngeun Park; Jung Nam Lee (Journal of Trauma and Injury)
Purpose Accurate and appropriate prehospital field triage is essential for a trauma system. The Korean trauma system (established in 2014) uses the trauma field triage algorithm of the United States Centers for Disease Control and Prevention (CDC). This study evaluated the suitability of the CDC field triage criteria for major trauma cases (injury severity score >15) in Korea. Methods This retrospective cohort study evaluated trauma patients who presented at the authors’ regional trauma center from January 1 to May 7, 2017. The undertriage and overtriage rates of each CDC field triage step were calculated. Receiver operating characteristic curves were constructed, and the area under the curve (AUC) was evaluated for each step. Results Among the 1,009 enrolled patients, 168 (16.7%) had major trauma. The undertriage/overtriage rates of each step (steps I, II, III, and IV) of CDC field triage were 9.2%/47.4%, 6.3%/50.8%, 4.5%/59.4%, and 5.3%/78.9%, respectively. The AUC values of each CDC triage step were 0.722, 0.783, 0.791, and 0.615, respectively. The AUC values of the separate components of each step (physiologic criteria, anatomic criteria, mechanism-of-injury criteria, and special considerations) were 0.722, 0.648, 0.647, and 0.456, respectively. Conclusions The CDC field triage system is acceptable, but not ideal, for Korean trauma care. If we follow the protocol, it would be preferable to omit step IV. The Korean Triage and Acuity Scale may be a good indicator for in-hospital triage. However, a new triage protocol that is simple to estimate on-scene while having good performance should be developed.